Dekodowanie zwrotów niedookreślonych na przykładzie przepisów nowelizujących ustawę o dostępie do informacji publicznej - Jabłoński, Mariusz (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The study raises issues of principles of correct legislation, especially the question of using by the legislature various vague legal terms. Detailed analysis refers to the provisions of the Act on public information, in scope of determining the meaning of issues: development and processing of information, provision of extracts, as well as the duty of provider of public information to take disproportionate activities that beyond simple operations. The author points out doubts connected with using these issues in terms of the constitutional principle of the specificity of legal provisions.
Keywords: ustawa o dostępie do informacji publicznej; zasada prawidłowego stanowienia prawa; konstytucyjna zasada określoności przepisów prawnych